Frequency of Vitamin Cobalamin Deficiency in Macrocystic Anemia Cases Reporting at Tertiary Care Hospital - Salman Khan, Javaria Amil, Husnain Hashim, Amanullah Khokhar, Dur E Huma, Tahir Mukhtar Syed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the frequency of vitamin cobalamin deficiency in macrocystic anemia cases reporting at tertiary care Hospital. Study Design: Cross-sectional Place and Duration: In Medicine department of DHQ Teaching Hospital, Sargodha and DHQ Hospital, Dera Ismail Khan for the duration of six months from August 2021 to January 2022. Methods: Total 210 cases of macrocytic anemia of both genders with ages 18-62 years were presented. Age, sex, and body mass index were among the specific demographics of the enrolled cases that were documented after receiving informed written consent. Ante-cubital fossa blood was sampled for 5 mL. To estimate the amount of vitamin cobalamin using an ELISA test kit, samples were centrifuged and sera were collected. SPSS 24.0 was used to analyze all data. Results: Among 210 cases, 130 (61.9%) were males and 80 (38.1%) females in this study. 70 (33.3%) cases had ages 18-35 years, 90 (42.9%) had ages 36-50 years and 50 (23.9%) had ages >50 years. Mean BMI of the presented cases was 24.66±14.49 kg/m2. We found that 180 (85.7%) patients had deficiency of cobalamin and 30 (14.3%) cases had normal cobalamin. Among 180 cases of cobalamin deficiency, 70 (38.9%) patients were severe, border line was found in 45 (25%) cases and deficient cases were 65 (36.1%). Conclusion: We concluded in this study that patients with macrocystic anemia had higher number of vitamin cobalamin deficiency found in 85.7% cases. Majority of the patients were deficient and had severe deficiency of cobalmin. Keywords: Vitamin Cobalamin, Macrocystic Anemia, Severe Deficiency